MEDALI RELASI ANTARGENERASI - Susanto, Meilisa Christiani; Liauw, Franky (Jurusan Arsitektur dan Perencanaan, 2024)
Intergeneration relationships have a distance that is created unconsciously from everyday life. Identical to the existence of different views, there is a clash that results in an intergeneration gap. Often referred to as the generation gap, it is a condition created due to differences in experiences and attitudes between generations, which ultimately results in a gap or distance. A bridge is needed to unify intergeneration perceptions, making each generation cherish each other and coexist. Play is then considered to be one of the ways that can bridge the intergeneration gap that has been created to date. In a game there are various goals, victory being the most commonly encountered goal. Trophies or medals are identical as a form of appreciation for winning a competition or game. Like playing, it is hoped that there will be a game of definition from the appreciation for victory. No longer in the form of physical things like medals but in the form of intergeneration relationships. Qualitative and comparative data collection methods from a collection of journals and books. The target of this research is to show the positive side of playing together between generations, in order to strengthen intergeneration relationships. Keywords: Cherish; Coexist; Intergeneration; Playing; Strengthen Abstrak Hubungan antargenerasi memiliki jarak yang tercipta tanpa disadari dari kehidupan sehari-hari. Identik dengan adanya perbedaan pandangan, terjadi benturan yang mengakibatkan kesenjangan antargenerasi. Sering disebut dengan kesenjangan generasi atau generation gap yang merupakan suatu kondisi yang tercipta karena adanya perbedaan pengalaman dan sikap antargenerasi, sehingga pada akhirnya menghasilkan kesenjangan atau jarak. Diperlukan jembatan untuk menyatukan persepsi antargenerasi, menjadikan setiap generasi saling menghargai dan hidup berdampingan. Bermain kemudian dianggap menjadi salah satu cara yang mampu menjembatani kesenjangan antargenerasi yang telah tercipta hingga saat ini. Dalam sebuah permainan ada berbagai tujuan, kemenangan menjadi tujuan yang paling sering ditemui. Piala ataupun medali identik sebagai bentuk apresiasi akan kemenangan atas suatu perlombaan atau permainan. Layaknya bermain, diharapkan terjadi permainan definisi dari bentuk apresiasi kemenangan. Tak lagi berupa hal fisik layaknya medali namun berwujud atas terjalinnya hubungan relasi antargenerasi. Metode pengumpulan data kualitatif dan komparatif dari kumpulan jurnal dan buku. Target penelitian ini agar dapat menunjukkan sisi positif dari bermain bersama antargenerasi, demi mempererat hubungan antargenerasi.